Developing PBL kit by utilizing blog in order to improve scientific process and problem solving skills in physics learning - Siti Maria Ulva (Jurnal Inovasi Pendidikan IPA, 2017)
The study aimed at generating PBL-based learning kit product by utilizing blog, at meeting the criteria of learning kit feasibility, at testing the effectiveness of learning kit that the researcher had developed and at identifying the learning participants’ scientific process and problem solving skills. In conducting the study, the researcher implemented the 4-D Model. The learning kit development started involved preliminary study, product design, expert and practitioner test, limited experiment and field experiment. The instruments that had been deployed in conducting the study consisted of validation sheet, learning management observation sheet, student response sheet, teacher interview sheet and learning results test. This study generated a product that consisted of lesson plan, teacher’s book, student’s book, student’s working sheet, blog and learning results assessment. The validation results showed that the learning kit that had been developed were feasible for implementation. Then, the experiment results showed that the learning kit that the researcher had developed met the criteria of effectiveness. Based on the pretest and the posttest results that was administered during the field experiment, students’ physics learning has increased approximately 17.10 point from the pretest average score, namely 58.20, and from the posttest average score, namely 75.30.